Tingkat Kebugaran Jasmani Pada Ekstrakulikuler Olahraga Di Sma Negeri 3 Cikampek - Leo Sukendar Nainggolan; Rahmat Iqbal; Rhama Nurwansyah Sumarsono (Peneliti.net, 2022)
The purpose of this study was to determine the level of physical fitness of participants in extracurricular sports at SMA Negeri 3 Cikampek. This study uses a survey method and uses a quantitative approach. The number of samples is 70 students consisting of 32 boys and 38 girls, the sampling technique used is purposive sample and the instrument used is TKJI 2010. Based on the results of data processing that has been calculated and analyzed by the researcher, the answer to the hypothesis that has been previously proposed by the researcher has been obtained. The results and conclusions of researchers on the level of physical fitness of sports extracurricular participants at SMA Negeri 3 Cikampek. Included in the very poor category. This is evidenced by the findings when physical fitness test activities are carried out. The results of the study stated that for the male category 15.6% were in the sufficient category, the less category was 43.8% and the very poor category was 40.6%, while for the female category 2.6% was in the sufficient category, the less category was 36.8%, and the very poor category is 60.5%. The conclusion of this study for the level of physical fitness of participants in extracurricular sports at SMAN 3 Cikampek is in the very poor category which is more dominant than the very good, good, sufficient, and poor categories.